2016
DOI: 10.1159/000449030
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Manifestation and Management of Autosomal Dominant Polycystic Kidney Disease in China

Abstract: Background: Autosomal dominant polycystic kidney disease (ADPKD) is the most common monogenic hereditary kidney disease characterized by progressive enlargement of renal cysts. The incidence is 1-2‰ worldwide. Mutations in two genes (PKD1 and PKD2) cause ADPKD. Currently, there is no pharmaceutical treatment available for ADPKD patients in China. Summary: This review focused on advances in clinical manifestation, gene diagnosis, risk factors, and management of ADPKD in China. There is an age-dependent increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Risk of bias ratings for each study were assessed with the NOS. In the domains of comparability, two studies of database analysis did not report characteristics and the comparability of both groups. In the domains of selection, all included studies were awarded full stars .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk of bias ratings for each study were assessed with the NOS. In the domains of comparability, two studies of database analysis did not report characteristics and the comparability of both groups. In the domains of selection, all included studies were awarded full stars .…”
Section: Resultsmentioning
confidence: 99%
“…Polycystic kidney disease (PKD), characterized by progressive growth of cysts from renal tubules, affects approximately 1‰–2‰ people worldwide . Autosomal dominant polycystic kidney disease (ADPKD) is the most common PKD and is the fourth leading cause of renal replacement therapy (RRT) . Nearly half of the ADPKD patients will progress to end‐stage renal diseases (ESRD) by the age of 60 as the kidney cysts grow .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive evidence suggests that normal measured glomerular filtration rate (mGFR) indexed for body surface area (BSA) may be slightly lower in young and middle-aged women than men. [1][2][3] A recent substudy of a US communitybased older cohort, Multi-Ethnic Study of Atherosclerosis (MESA-Kidney), reported a 12% lower mGFR in women than men. 4 This difference was not observed in a prior substudy of an Icelandic community-based older cohort, Aging Genes Environment Susceptibility (AGES-Kidney), using similar methods for GFR measurement.…”
Section: Research Letter Effects Of Body Size and Composition On Sex mentioning
confidence: 99%
“…Autosomal dominant polycystic kidney disease (ADPKD) is the most frequently inherited kidney disease; its incidence has been reported to be 1/400 to 1/2,500 worldwide and 1.5 million individuals are affected in China (1)(2)(3)(4). A common cause of ADPKD is a mutation in polycystin (PC)-1, a transient receptor potential channel which interacts with (PKD1) and/or PKD2, and accounts for 85 and 15% of all detectable cases of ADPKD, respectively.…”
Section: Introductionmentioning
confidence: 99%